PROFILE OF ADOLESCENT INTERPESONAL RELATIONS IN HIGH SCHOOL IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Marsela, Fitra; Bahri, Syaiful (EDUCATIONE, 2023)
Teenagers are the next generation of the nation whose development does not go unnoticed. One of the developments in the spotlight in the era of the industrial revolution 4.0 is the ability to relate socially or better known as interpersonal relationships. This study aims to provide a profile of students' interpersonal relationships in the industrial revolution 4.0 era which is synonymous with performance competition, ability to work in teams and have the ability to work together in teams. This research uses quantitative descriptive research. The subjects that are the focus of this study are 115 teenagers in class X SMA Negeri 5 Banda Aceh. Collecting data using interpersonal relationship scale. Analysis of research data using descriptive analysis, which consists of: (1) data examination; (2) data classification; (3) data tabulation; (4) calculate the frequency of data; (5) determine the category. This study can be used as a reference for teacher guidance and counseling in schools in developing adolescent interpersonal relationships. The results of the study indicate that the level of interpersonal relationships in general is in the high category. This can be seen from the number of teenagers' answers, which in general are 112 teenagers or 97% are in the high category. A total of 3 adolescents or 3% are in the moderate category and no adolescents are in the low category.